2024
DOI: 10.1002/app.55487
|View full text |Cite
|
Sign up to set email alerts
|

An applicability study on various methods for determining the monomer conversion rate of polyamide 6

Zhihao Gao,
Renhai Zhao,
Shunzhong Cai
et al.

Abstract: Anionic ring opening polymerization of ε‐caprolactam (CL) results in the formation of high molecular weight polyamide 6 (PA6) within a few minutes. The monomer conversion rate is an important characterization parameter for polymerization process as well as the end products. This paper used PA6 films with different polymerization degrees as research object for the first time, and systematically compared the performance of four methods for measuring CL conversion rate. The analytical methods were solvent extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Due to the formation of the first network, L-P(BA- co -GMA) b is difficult to dissolve in deuterium reagents, so we tested the monomer conversion by the weighing method, cleaned with ethanol after polymerisation and completely removed the solvent at high temperature, and then compared with the quality of the added monomer. 45 We found that the monomer conversion rate was over 98% (Fig. S7†).…”
Section: Resultsmentioning
confidence: 86%
“…Due to the formation of the first network, L-P(BA- co -GMA) b is difficult to dissolve in deuterium reagents, so we tested the monomer conversion by the weighing method, cleaned with ethanol after polymerisation and completely removed the solvent at high temperature, and then compared with the quality of the added monomer. 45 We found that the monomer conversion rate was over 98% (Fig. S7†).…”
Section: Resultsmentioning
confidence: 86%